2006
DOI: 10.2139/ssrn.910226
|View full text |Cite
|
Sign up to set email alerts
|

Bank Market Power and SME Financing Constraints

Abstract: Theoretical models of lending and industrial organization theory predict that firm access to credit depends critically on bank market structure. However, empirical studies offer mixed results. Some studies find that higher concentration is associated with higher credit availability consistent with the information hypothesis that less competitive banks have more incentive to invest in soft information. Other empirical studies, however, find support for the market power hypothesis that credit rationing is higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 102 publications
3
23
0
Order By: Relevance
“…The empirical results are mixed, with some studies finding generally unfavorable effects from market power (e.g., Elsas, 2005;Karceski et al, 2005;Cetorelli and Strahan, 2006), and others finding favorable effects (e.g., Petersen and Rajan, 1995;Cetorelli and Gambera, 2001;Bonaccorsi di Patti and Dell'Ariccia, 2004;Cetorelli, 2004). 12 One study found that the results depend on how market power is measured with concentration measures and the Lerner index generally showing conflicting results (Carbó -Valverde et al, 2006).…”
Section: Market Competitionmentioning
confidence: 99%
“…The empirical results are mixed, with some studies finding generally unfavorable effects from market power (e.g., Elsas, 2005;Karceski et al, 2005;Cetorelli and Strahan, 2006), and others finding favorable effects (e.g., Petersen and Rajan, 1995;Cetorelli and Gambera, 2001;Bonaccorsi di Patti and Dell'Ariccia, 2004;Cetorelli, 2004). 12 One study found that the results depend on how market power is measured with concentration measures and the Lerner index generally showing conflicting results (Carbó -Valverde et al, 2006).…”
Section: Market Competitionmentioning
confidence: 99%
“…Claessens and Laeven (2005) provides evidence for 16 countries that more competitive banking systems exert a positive effect on firms' access to finance. Carbo-Valverde et al (2009) shows that the effect of banking sector competition on Spanish firms' access to finance depends crucially on how competition is measured. Their results indicate a negative association between market power and access to finance when the Lerner index is used.…”
Section: Introductionmentioning
confidence: 99%
“…These models assume that the credit market may be in disequilibrium and, therefore, the observed interest rate does not ensure that credit demand is equal to credit supply. Ogawa and Suzuki (2000), Atanasova and Wilson (2004), Shikimi (2005) and Carbo-Valverde et al (2009) estimated disequilibrium models to identify the presence of credit rationing in the economy. More recently, Kremp and Sevestre (2013) considered this methodology to analyze the determinants of credit demand and credit supply for French small and medium-sized enterprises (SMEs) and found that, even though banks adopted tighter standards in credit approval, French firms were not significantly affected by credit rationing, even after 2008.…”
Section: Introductionmentioning
confidence: 99%